Press Freedom And Hoax: Democracy Anomaly - Ibnu Sina Chandranegara (NOMOI Law Review, 2020)
AbstractAfter the collapse of the New Order regime, the hope of a more realized configuration gave freedom of approval through apress. However, the freedom obtained by the Press is currently full of negatives, namely news of false news that is increasing. The method used in this study is a normative juridical legal research method. According to the results of the 2018 Edelman Trust Barometer survey, seven out of 10 people in the world were worried that fake news would be used as